2006
DOI: 10.1016/j.ijid.2004.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of brucellosis in the rural area of Kayseri, Central Anatolia, Turkey

Abstract: In this case, intravenous and intrathecal colistin infusions were tolerated well and without any serious adverse effects. The intrathecal infusion regimen was decided according to the company's recommendations, with some necessary modifications due to early signs of reversible neurotoxicity. One year later the patient is very well, with no residual neurological manifestations.In conclusion, intravenous and intrathecal colistin may be a good therapeutic option in the treatment of meningitis due to multidrug-res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
40
5
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 8 publications
(11 reference statements)
3
40
5
4
Order By: Relevance
“…About 4.96% prevalence of brucellosis has been reported among PUO and occupationally exposed individuals in Goa [18], 24.5% in Ludhiana, India [19]. Globally several studies showed the similar seroprevalence such as 6.4% in Iran [20], 5.2% in Afghanistan [21], 3.4% in Central Anatolia [22], 19% in Saudi Arabia [23], 53.25% in Mongolia [24], 20.5% in Tanzania [25], 6.26% in Egypt [26], 16% in Kenya [27], 2.15% in Ethiopia [28], 24.1% in abbatoir workers of Abuja [29], 17% in Uganda [30] and 3.8% in Chad [31].…”
Section: Discussionmentioning
confidence: 94%
“…About 4.96% prevalence of brucellosis has been reported among PUO and occupationally exposed individuals in Goa [18], 24.5% in Ludhiana, India [19]. Globally several studies showed the similar seroprevalence such as 6.4% in Iran [20], 5.2% in Afghanistan [21], 3.4% in Central Anatolia [22], 19% in Saudi Arabia [23], 53.25% in Mongolia [24], 20.5% in Tanzania [25], 6.26% in Egypt [26], 16% in Kenya [27], 2.15% in Ethiopia [28], 24.1% in abbatoir workers of Abuja [29], 17% in Uganda [30] and 3.8% in Chad [31].…”
Section: Discussionmentioning
confidence: 94%
“…The incidence of brucellosis in Turkey has been reported to be 1% to 26.7% in various studies, with changing ratios in different regions [8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…Bu verilere göre bruselloz olgu sayısı gerçekte Sağlık Bakanlığına bildirilenden fazladır. 5,6 Hastalığın sık görüldüğü illerden biri olan Konya'da, toplumun bulaş ve korunma yolları ile ilgili bilgilerin değerlendirildiği bir çalışmada, katılımcıların %43,6'sının bulaşma yollarından en az birini doğru olarak bildiği; %14'ünün konu hakkında bilgisi olduğunu ifade etmesine rağmen verdiği yanıtların yanlış olduğu; %32,4'ünün ise konu ile ilgili sorulara yanıt veremediği bildirilmiştir. 7 Akdeniz bölgesinde yapılan, olgu serilerinin incelendiği bir diğer çalışmada yöre halkının hastalığı ve bulaş yollarını bilmelerine karşın kaynatılmadan üretilen süt ürünlerinin tüketiminin önlenemediğini belirterek halkın eğitimi üzerinde daha titizlikle durulması gerektiği sonucuna varılmıştır.…”
Section: Discussionunclassified
“…1,[6][7][8][9][10] Bruselloz tedavisinde kombine ve uzun süreli antibiyotik kullanmak gerekmektedir. DSÖ'nün önerdiği klasik rejim, doksisiklin ve rifampisinin altı hafta kullanımıdır.…”
Section: Discussionunclassified